2018
DOI: 10.1002/erv.2576
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Eating Disorder Psychopathology within the Treatment Seeking Transgender Population: The Role of Cross‐Sex Hormone Treatment

Abstract: Many transgender people experience high levels of body dissatisfaction, which is one of the numerous factors known to increase vulnerability to eating disorder symptoms in the cisgender (non-trans) population. Cross-sex hormones can alleviate body dissatisfaction so might also alleviate eating disorder symptoms. This study aimed to explore risk factors for eating disorder symptoms in transgender people and the role of cross-sex hormones. Individuals assessed at a national transgender health service were invite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 58 publications
(92 reference statements)
1
59
0
Order By: Relevance
“…One study showed that following GAHT, MTFs experienced less body uneasiness, but FTMs did not share the same benefit, possibly due to discomfort at a personal rather than social level [54]. The rest of the studies strongly established that GAHT reduces body discomfort and increases body-gender congruence and body image satisfaction, most likely due to a reduction of the discrepancy in characteristics between natal sex and gender identity [35•, 39,42, 43, 48, 55, 56]. Finally, noticeable decreases in eating disorder psychopathology and symptoms were documented by Testa et al [55] and Jones et al [56], although Turan et al [39] did not find a correlation between GAHT and eating attitudes or behaviors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study showed that following GAHT, MTFs experienced less body uneasiness, but FTMs did not share the same benefit, possibly due to discomfort at a personal rather than social level [54]. The rest of the studies strongly established that GAHT reduces body discomfort and increases body-gender congruence and body image satisfaction, most likely due to a reduction of the discrepancy in characteristics between natal sex and gender identity [35•, 39,42, 43, 48, 55, 56]. Finally, noticeable decreases in eating disorder psychopathology and symptoms were documented by Testa et al [55] and Jones et al [56], although Turan et al [39] did not find a correlation between GAHT and eating attitudes or behaviors.…”
Section: Resultsmentioning
confidence: 99%
“…The rest of the studies strongly established that GAHT reduces body discomfort and increases body-gender congruence and body image satisfaction, most likely due to a reduction of the discrepancy in characteristics between natal sex and gender identity [35•, 39,42, 43, 48, 55, 56]. Finally, noticeable decreases in eating disorder psychopathology and symptoms were documented by Testa et al [55] and Jones et al [56], although Turan et al [39] did not find a correlation between GAHT and eating attitudes or behaviors. Since all three of these studies—only one [39] of which was longitudinal (Table 1)—were conducted in different countries (USA, Canada, UK, Turkey) using different questionnaires, cross-cultural comparison among these data should be approached cautiously.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, qualitative reports from women with ASD often report conflict between expected feminine roles and their autistic identities [77]. At the same time, transgender individuals are at increased risk of body dissatisfaction and clinical EDs [78,79]. Specifically, restrictive eating and exercise can be a means of achieving a body congruent with one's gender identity [80].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Castellano and colleagues [ 73 ] reported no difference between the transgender population and their matched controls. This could be due to the fact that people undergoing GAGS are generally already on CHT and hormonal treatment is known to have a positive effect on body image [ 10 , 36 , 88 ] by aiding in the development of desired secondary sexual characteristics of the experienced gender, whilst helping to alter some of the attributes relative to the sex assigned at birth. Consequently, this leads to an improvement in body image-related QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Studies regarding general QoL have found that transgender people’s QoL is poorer than that of cisgender people, but that it improves post-GAT. The poorer QoL found in the transgender population pre-CHT [ 56 , 74 ] could be explained by the high degree of mental health problems reported in this population [ 16 , 89 ] as well as by the difficulties that many have in socialising and living a fulfilling life [ 10 12 , 37 ]. However, the studies that focus only on people pre-CHT were rare and only included those seeking medical transition, which does not allow for a generalisation of these findings to the general transgender population.…”
Section: Discussionmentioning
confidence: 99%